Predictive genetic testing: mediators and moderators of anxiety. - Michie S; French DP; Marteau TM (International Journal of Behavioral Medicine, 2002)
Mediators and moderators of anxiety following predictive genetic testing were investigated in a cross-sectional study of 208 individuals at risk for familial adenomatous polyposis (FAP). Receiving a positive test result was associated with increased anxiety. The relationship between test result and anxiety was mediated by how threatened individuals felt by their test results. The impact of a positive test result was greater for those who felt distressed about FAP in their families, perceived FAP to be more serious, and perceived the genetic test to be more accurate. The results suggest that assessing, and possibly modifying, people's appraisals of the condition and of its impact on the family and of the threat of the genetic test may help to reduce subsequent anxiety. This has implications for the practice of genetic counseling.